Dampak penghasilan istri pada kepuasan pernikahan dewasa - Rumondor, Pingkan C. B.; Paramita, Greta Vidya; Francis, Nangoi Priscilla; Geni, Putri Lenggo (Jurnal Psikologi Ulayat: Indonesian Journal of Indigenous Psychology, 2013)
The current study aims to assess the effect of wife income to marital satisfaction among dual career young urban couples. Marital satisfaction is deined as a individual’s subjective experience toward marriage or components within a marriage. The scale consists of 38 items measuring individual’s satisfaction in communication, division in roles, agreement, openness, intimacy, intimacy in social relationship, sexuality, finance, and spirituality. The results indicate that the instrument was found to be reliable (α= 0.967) and showcorrelation with subjective rating of overall marital satisfaction (r =0.293,p<0.05).The result come up from the study showed no effect of wife income to marital satisfaction in dual career young urban couples (p > 0.05).